Extraction of Ga(III) by Di‐(2‐ethylhexyl)phosphoric acid (D2EHPA)‐Modified XAD‐4 Resins Prepared by Solvent‐Nonsolvent Modification. Issue 12 (9th November 2021) - Chen, Jyh-Herng; Chang, Yu-Hao; Hsu, Kai-Chung; Lin, Jing-Chie
Abstract: Gallium (Ga) is one of the most important elements that are widely used in electronic devices. The development of Ga recovery technology is an important issue for resource recycling. In this study, di‐(2‐ethylhexyl)phosphoric acid (D2EHPA)‐modified XAD‐4 resin (DMR) is prepared by the solvent‐nonsolvent method. The evolution of pore characteristics demonstrates that the solvent‐nonsolvent treatment is advantageous for the immobilization of D2EHPA in XAD‐4 resin. The adsorption isotherm of Ga(III) can be described by the Langmuir isotherm model. The Ga(III) adsorption kinetics follows the pseudo‐second‐order model. The immobilized D2EHPA shows good stability. The reusability study indicates that DMR can maintain the performance after three cycles of adsorption and stripping. The results for the treatment of a practical leaching solution from GaN/Al2 O3 wafer further demonstrate that DMR can be applied effectively for Ga(III) recovery. Abstract : Di‐(2‐ethylhexyl)phosphoric acid (D2EHPA)‐modified XAD‐4 resins (DMR) were prepared by the two‐step solvent‐nonsolvent method and the adsorption characteristics of Ga(III) onto DMR were investigated. D2EHPA is well‐suited as an extractant since it provides good efficiency in recovery and separation of Ga(III) from aqueous solutions. The immobilized D2EHPA exhibits satisfactory stability.